Pengembangan Sistem Informasi Feedback Pelanggan Hosting Pada CV. E-Padi Corporation Berbasis Web - Afrizal Afrizal; Fitriani Fitriani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2017)
One of the tasks of e-padi.com company is to make customer friendly service that is by making service feedback for product or service that have been bought by customer. At this time the feedback service that has been run still using the system of phone calls and sms. Service using the phone is a practical service performed by the customer and get a fast response from the service provider. However, the service using the phone or sms does not provide a recap or record of feedback from customers or companies. The purpose of this information system development is to design and build a customer feedback system based computer hosting systematic, structured and directed at the CV. E-Padi Corporation. Customer feedback information system generated to process Domain data and hosting customers, especially on the corporate environment CV. E-Padi Corporation with the results of form data user, Domain, hosting and feedback. The resulting report is customer feedback data and overall customer data. Web-based presentation with PHP programming and mySQL database.